2005
DOI: 10.1007/s11064-005-2608-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Protein Kinase C and Cyclic AMP in the Ammonia-Induced Shift of the Taurine Uptake/Efflux Balance Towards Efflux in C6 Cells

Abstract: A previous study showed that treatment of C6 glioma cells with 10 mM ammonium chloride monia") for 24 h decreases taurine uptake and evokes sodium-dependent taurine efflux, indicating reversal of the taurine transporter (TauT)-mediated transport as an underlying mechanism. Consistent with the involvement of TauT we now show that the ammonia-induced changes in Tau uptake and efflux are inhibited by the protein kinase C (PKC) activator phorbol 12,13-dibutyrate (PDBu). Ammonia treatment of C6 cells resulted in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Hyperammonemia in glial cells results in increased cellular levels of calcium and cAMP [3], [9], [51], [70]. Both calcium and cAMP have been proposed to mediate S100B release [71], [72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperammonemia in glial cells results in increased cellular levels of calcium and cAMP [3], [9], [51], [70]. Both calcium and cAMP have been proposed to mediate S100B release [71], [72].…”
Section: Discussionmentioning
confidence: 99%
“…Acute ammonia neurotoxicity can be mediated by an excitotoxic mechanism involving the glutamatergic system, including elevation of extracellular glutamate content, decreased glutamate transporters, NMDA receptor activation and subsequent increases in intracellular calcium concentration [3], [4], [5], [6], [7]. Metabolic effects of ammonia neurotoxicity include changes in reactive oxygen and nitrogen species (ROS/RNS) levels [8], nitric oxide (NO) metabolism [2], cAMP levels [3], [9], mitogen-activated protein kinase (MAPK) pathway [10], cytoskeleton [11] and astrocyte swelling [12]. Moreover, ammonia toxicity also induces increase in tumor necrosis factor α (TNF-α), Interleukin 1β (IL-1β), which can be associated to ROS production and involve protein kinase A (PKA), extracellular signal-regulated kinase (ERK) and nuclear factor-κB (NF-κB) activation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia elevates intracellular cAMP levels in cultured Müller glia (Faff et al ., 1997), in C6 glioma cells (Zielińska et al ., 2005) and in Dictyostelium (Williams et al ., 1993). In the present study, we found not only that ammonia increases cAMP but also that cAMP promotes apoptosis in the murine microglial cell line BV‐2.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the failure of ammonia-induced M€ uller cell swelling was not caused by triggering endogenous glutamate signaling. Another possibility was that ammonia induces the release of taurine from the cells (Faff et al, 1996); ammonia-induced efflux of taurine via the taurine transporter (Zieli nska et al, 2005) might compensate the osmotic gradient across glial membranes. However, the taurine transporter inhibitor, guanidinoethylsulfonate, did not induce osmotic swelling of M€ uller cell bodies in the presence of ammonia (Fig.…”
Section: Ammonia Does Not Induce Acute Swelling Of Retinal Glial and mentioning
confidence: 99%